2020
DOI: 10.4049/jimmunol.2000459
|View full text |Cite
|
Sign up to set email alerts
|

Zbtb20 Restrains CD8 T Cell Immunometabolism and Restricts Memory Differentiation and Antitumor Immunity

Abstract: CD8 T cell differentiation is orchestrated by dynamic metabolic changes that direct activation, proliferation, cytotoxic function, and epigenetic changes. We report that the BTB-ZF family transcriptional repressor Zbtb20 negatively regulates CD8 T cell metabolism and memory differentiation in mice. Effector and memory CD8 T cells with conditional Zbtb20 deficiency displayed enhanced mitochondrial and glycolytic metabolism, and memory CD8 T cells had enhanced spare respiratory capacity. Furthermore, Zbtb20-defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 76 publications
1
18
0
Order By: Relevance
“…ZBTB20 is widely expressed in hematopoietic tissues, and promotes the long-term antibody responses by increasing the survival of BM plasma cells ( 22 ). ZBTB20 is transiently upregulated in activated CD8 + T cells, and in the steady state, its levels in CD8 + T-cell compartment are CD62L + CD44 + Tcm > CD62L - CD44 + Tem ≈ CD62L + CD44 - Tn > CD62L - CD44 - Te cells ( 178 ). Depletion of ZBTB20 in activated CD8 + Te cells, mediated by Gzmb -Cre, enhances the cellular glycolytic and mitochondrial metabolisms, and increases their mitochondrial fuel flexibility.…”
Section: Zbtb Proteins Mainly Affecting the Function Of T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…ZBTB20 is widely expressed in hematopoietic tissues, and promotes the long-term antibody responses by increasing the survival of BM plasma cells ( 22 ). ZBTB20 is transiently upregulated in activated CD8 + T cells, and in the steady state, its levels in CD8 + T-cell compartment are CD62L + CD44 + Tcm > CD62L - CD44 + Tem ≈ CD62L + CD44 - Tn > CD62L - CD44 - Te cells ( 178 ). Depletion of ZBTB20 in activated CD8 + Te cells, mediated by Gzmb -Cre, enhances the cellular glycolytic and mitochondrial metabolisms, and increases their mitochondrial fuel flexibility.…”
Section: Zbtb Proteins Mainly Affecting the Function Of T Cellsmentioning
confidence: 99%
“…Depletion of ZBTB20 in activated CD8 + Te cells, mediated by Gzmb -Cre, enhances the cellular glycolytic and mitochondrial metabolisms, and increases their mitochondrial fuel flexibility. Importantly, ZBTB20-deficiency renders CD8 + T cells, both phenotypically and transcriptionally, toward memory cells with an enhanced ability to mount secondary responses ( 178 ). Thus, ZBTB20 represents an important regulator that restrains CD8 + T cell metabolism and Tm differentiation in mice ( Figure 2B ).…”
Section: Zbtb Proteins Mainly Affecting the Function Of T Cellsmentioning
confidence: 99%
“…2B) (37). Zbtb20 expression was also shown in a subpopulation of memory T-lymphocytes (38). To our knowledge there is no evidence for Zbtb20 expression in the granulocyte lineage and other T-lymphocytes.…”
Section: Zbtb20 Expression In Immune Cellsmentioning
confidence: 79%
“…ZBTB20 is a transcriptional repressor with multiple functions, such as regulating inflammation, cell death, immunity and so on. 42 , 43 A study indicated that mice lacking ZBTB20 displayed abnormal growth rate, accompanied by high fatality and infertility, emphasizing the importance of ZBTB20 in organisms. 44 In another study, ZBTB20 knockout could effectively protect mice from endotoxin shock and sepsis and further analysis showed that ZBTB20 may function through promoting NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%